Dampak Penerapan Peraturan Pemerintah Nomor 58 Tahun 2023 Terhadap Efektifitas Pemotongan Pajak oleh Bendaharawan Pemerintah - Yunia Reza Herawati; DWITA HARTIKA PUTRI; JAMILATUL QAMARIYAH; YUNITA TRI FAUZIYAH; MILA SARI; Moh. Faisol (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2025)
This research aims to determine the impact of TER implementation on the effectiveness of withholding Income Tax 21 on government treasurers. This research method uses qualitative case studies. The informants of this research are seven government treasurers. The data analysis uses qualitative data analysis developed by Miler and Huberman. The results of this study provide an overview of how implementing PP 58/2023 for government treasurers in Sumenep Regency delivers convenience in calculating withholding Income Tax 21. This convenience is in the form of simplicity in the calculation structure based on gross income every month, except in the last month, and the availability of the e-bupot 21/26 information system on the djponline page. However, some government treasurers disagree with this and consider PP 58/2023 not to make it easier because every month, the treasurer must identify every change in each team member's gross income because the tariff layers charged are different. This study implies that the amount of benefits received from a policy by